COMPANY REGULATION DEVELOPMENT ASSISTANCE ON PT. GLOBAL CIPTAPRIMA BASED ON THE PROVISIONS OF LABOR LAW - Hana Renata Tan Peiru; Winda Fitri (ConCEPt - Conference on Community Engagement Project, 2022)
The company was created based on the provisions of the applicable law. The purpose of forming a company is to obtain a profit or earn a profit. In running a company, it is necessary to have an order so that the company can be well known and develop. Therefore, a rule is made which is better known as company regulations. Company regulations are regulations made in writing by employers that contain work requirements and company rules and regulations. company regulations must be made by companies that have employed at least 10 (ten) workers. the company regulations regulate the working conditions applicable in the company, containing the rights and obligations for workers and entrepreneurs in order to obtain legal certainty. The implementation method that the author uses is using interview techniques conducted with the President Director and employees of PT. Global Ciptaprima.